Early‐onset colorectal cancer in young adult survivors of childhood cancer. Issue 7 (13th April 2016) - Morita, Daisuke; Nakazawa, Yozo; Tanaka, Miyuki; Nakayama, Yoshiko; Koizumi, Tomonobu; Koike, Kenichi
Abstract: We describe the cases of two childhood cancer survivors (CCS) who developed colorectal cancer at 21 and 30 years of age. They had been treated with 30 Gy abdominal irradiation and chemotherapy including platinum and high‐dose alkylating agents at age 1 year, and 12 Gy total body irradiation and high‐dose cyclophosphamide at age 15 years, respectively. Both had not been screened for colorectal cancer. One patient with advanced cancer died, whereas the other with early cancer was still alive at the time of writing. Two guidelines for long‐term follow‐up of CCS recommend that CCS who had >30 Gy irradiation receive periodic check‐ups at age ≥ 35 years. The present cases suggest that CCS, even with irradiation <30 Gy, should receive earlier check‐ups for colorectal cancer. © 2016 Japan Pediatric Society